Effect of Sustainable Development and Institutional Quality on Growth - Har, Wai Mun; Sin, Mei Chen (Studia Ecologiae et Bioethicae, 2023)
The issue of compatibility of sustainable development policies, institutional quality, and economic growth gains on importance as the world races towards achieving the 2030 Agenda for Sustainable Development. This paper aims to examine the relationship between sustainable development, institutional quality, and economic growth between the years 2012 and 2021 in 116 countries. The quantile regression method has been employed in this study to capture various relationship nexuses in different quantiles of growth. The common 15th, 25th, 50th, 75th and 95th quantiles have been selected. The official Sustainable Development Goals (SDG) Index is applied to proxy the holistic conceptualization and policy achievement of the United Nation’s SDGs. The findings show a negative relationship between sustainable development and economic growth, indicating that achieving sustainable development goals will harm the economic growth. Increasing negative coefficient values from lower to higher quantiles imply increasing opportunity cost of degrowth towards increasing sustainable development. Besides, institutional quality did not affect economic growth, either directly or indirectly. The study suggests the necessity to review the existing policies, institutional structures, and strategies to foster compatibility between sustainable development, institutional quality, and growth.